Electro-catalytic conversion of ethanol doped with lithium and sodium manganese dioxide electrode - Сокольський, Г.В.; Іванова, Н.Д.; Іванов, С.В.; Болдирєв, Є.І.; Кобилінська, О.В.; Демченко, М.В. (Proceedings of National Aviation University (archive), 2009)
Manganese dioxide samples have been prepared by the anode electrodeposition. The electrocatalytic activity of products obtained was investigated by the method of voltammetry for ethanol oxidation. The analysis of influence of additives of Li+ and Na+ on electrocatalytic activity of the obtained samples is carried out.